2013
DOI: 10.1007/s00276-013-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon trajectory variations of the mandibular canal and of the mandibular incisive canal: case report

Abstract: The advent of CBCT in Dentistry allowed a greater accuracy in the diagnosis of anatomical variations in the jaws, preventing injury to the neurovascular bundle and enabling an adequate surgical planning in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Any complication was related with these anatomical variations. 5 Similar to our finds, was reported two clinical cases with fenestration in posterior area, both in a CBCT exam evaluation to dental implant placement. 8 One case was found in a 58-year-old woman, located in left mandibular body, while the other was in a 68-year-old man billaterally also in mandibular body.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Any complication was related with these anatomical variations. 5 Similar to our finds, was reported two clinical cases with fenestration in posterior area, both in a CBCT exam evaluation to dental implant placement. 8 One case was found in a 58-year-old woman, located in left mandibular body, while the other was in a 68-year-old man billaterally also in mandibular body.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] Sometimes, the mandibular canal (MC) course is close to the roots of the teeth or to the lower border of the mandible, 4 and MC anatomical or trajectory variation has been described. [3][4][5] Even though textbooks do not provide a detailed description of the MC course, it has been reported that nerve and vascular bundles may be close to the buccal cortex. It was related that 7% of the MC are in contact to mandible buccal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…difficulties facing the clinician [2,6,10,13,24]. In addition, few studies focus on describing these morphological variations of the MC on different samples of populations to report interesting data like morphological configurations and its prevalence.…”
Section: (11%)mentioning
confidence: 99%
“…The mandibular canal (MC) extends bilaterally from the mandibular foramen to the mental foramen [6,12,19]. It runs longitudinally through the spongy tissue of the bone in an anteroinferior direction and describes a concave anterosuperior curve [7,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation